Transvesical endoscopic peritoneoscopy: a novel 5 mm port for intra-abdominal scarless surgery - Lima, E (2006)
PURPOSE:Recently various groups reported successful attempts to perform intra-abdominal surgery through a transgastric pathway. We assessed the feasibility and safety of a novel transvesical endoscopic approach to the peritoneal cavity through a 5 mm port in a porcine model.MATERIALS AND METHODS:Transvesical endoscopic peritoneoscopy was performed in 8 anesthetized female pigs, including 3 nonsurvival and 5 survival animals. Under cystoscopic guidance a vesical hole was created on the ventral bladder wall with an open-ended ureteral catheter. An over tube with a luminal diameter of 5.5 mm was placed in the peritoneal cavity, guided by a 0.035-inch guidewire. In all animals we performed peritoneoscopy of the entire abdomen as well as liver biopsy and falciform ligament section. A vesical catheter was placed for 4 days in all survival animals, which were sacrificed by day 15 postoperatively.RESULTS:After a learning curve in the first 3 nonsurvival animals the creation of a vesical hole and placement of the over tube were performed without complication in all survival animals. In these animals we easily introduced an EndoEYEtrade mark into the peritoneal cavity, which provided a view of all intra-abdominal viscera, as well as a 9.8Fr ureteroscope, which allowed simple surgical procedures without complications. In survival experiments all pigs recovered. Necropsy examination revealed complete healing of the vesical hole and no signs of infection or adhesions into the peritoneal cavity.CONCLUSIONS:Transvesical endoscopic peritoneoscopy was technically feasible and it could be safely performed in a porcine model. This study provides encouragement for additional preclinical studies of transvesical surgery with or without combinations with other natural orifices approaches to design new intra-abdominal scarless procedures in what seems to be third generation surgery.